(untitled) (LACCEI, 2024)
Nostoc sp. is a species with attractive biotechnological potential for the industry, with limitations due to its low natural production. The present study aimed to determine the total dissolved metals in the water bodies where Nostoc "Cushuro" grows, in three high Andean areas of the La Libertad Region: Caserío Urupampa, Laguna Verde Oscorgon and Laguna Cushuro, during the months of November and December 2019. Total metals were determined using the EPA-Method 200.7 Rev. 4.4 method by ICP, finding values below the maximum permissible limit except for phosphorus in the sample from Caserío Urupampa because it is an area with greater exposure to the movement of people and animals, which are a source of organic phosphorus. Nostoc parmeloides, Nostoc sphaericum and Nostoc commune species were found, demonstrating their ability to adapt to different conditions.